LEGAL EFFECTS OF ADOPTION ON THE ADOPTED PARENTS' INHERITANCE - Nusantara Tarigan Silangit (LPPM YPITI, 2026)
Adoption of a child will have legal consequences for both the child being adopted and the person adopting it. One of the legal consequences is the inheritance of the parents who adopted the child if they die. The position of adopted children cannot be equated with biological children because adopting a child according to statutory regulations or Islamic law does not sever the adopted child's blood/lineage relationship with the biological family, but only a transfer of responsibility from the biological parents to the adoptive parents. Adoption does not change the legal, lineage and mahram relationship between the adopted child and the biological parents or adoptive parents. The procedure for adopting a child in the Compilation of Islamic Law (KHI) is to make a letter requesting adoption which is signed by the applicant or his attorney. The part of an adopted child's inheritance in the Compilation of Islamic Law (KHI) is that the adopted child and his or her adoptive parents do not inherit each other.